(untitled) (Journal of Partial Differential Equations, 2020)
"This paper is devoted to the study of a nonlinear anisotropic elliptic equation with degenerate coercivity, lower order term and L^1 datum in appropriate anisotropic variable exponents Sobolev spaces. We obtain the existence of distributional solutions."